Different Schemes Launched by the Government for Achieving the Aims of Universalization of Elementary Education: Exploring Government Schemes for Universalizing Elementary Education (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Education is very essential for every human being. It was natural with the birth of mankind and till the human race survived, it will continue to work. Through education man becomes 'man' and role model for society. Education cannot be feasible without knowledge and education is the only tool that can deal with most of human problems, because it gives people chance to improve their skills to move towards the development of the direction. Since education is important for the growth of a developing nation like India, many steps have been taken to increase the number of kids enrolled for education. Education has been made an essential and fundamental part of national development efforts. After independence, an effort has been complete to spread education at all levels of Indian society. To fortify the Indian training framework, instructive approaches and different plans are embraced by the legislature to accomplish the points of Universalization of Elementary Education (UEE) because of these plans, foundation improvement at the school level at huge scale. It has expanded the nature of training and also rivalry. But different studies show that it cannot help in improving the level of knowledge. It has also taken various steps for the reform and expansion of the government, which is indispensable for the development of the nation. This paper also explains outlines the various schemes and programs launched by government for achieving the aims of universalization of elementary education